Nation building & Māori development in the 21st century: conference proceedings, 30th August to 1st September 2000. - University of Waikato School of Māori and Pacific Development (School of Māori and Pacific Development, The University of Waikato, 2001)
Keywords: economic conditions; government; māori development; self-determination; sovereignty

Chapter 9: Rongotai: the Roar of the Ride: Māori in Parliament - Durie, Mason (Ngā tai matatū: tides of Māori endurance, 2005)
"Nga Tai Matatu: Tides of Maori Endurance describes and analyses the position of the Maori people and Maori interests at the start of the third millennium. It also recognises the journeys from the past and makes projections into the future. The book builds on the highly successful Te Mana, Te Kawanatanga: The Politics of Maori Self-Determination but also introduces new issues and canvasses recent developments that have influenced Maori lives and Maori resources. Development is an ongoing process that has distant beginnings and no real ending. That sense of eternity is reflected in the Maori title; like the changing nature of the tide, Maori fortunes also change."–Book jacket.
Keywords: government relations; kāwanatanga; law; mana motuhake; māori electorates; māori seats; parliament; self-determination; sovereignty; tino rangatiratanga

Te mana, te kāwanatanga: the politics of Māori self-determination - Durie, Mason (Oxford University Press, 1998)
Keywords: government relations; kāwanatanga; law; self-determination; sovereignty; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

Voting in Māori Governance Entities - Bargh, Maria; Rata, Arama (The International Indigenous Policy Journal, 2020)
Internationally, declining voter turnout is a topic of considerable concern in many liberal democracies. In this article, we investigate whether these similar trends can be discerned in the voter turnout for Māori governance entities. We first explore some of the demographic contexts within which Māori governance entities operate with a specific focus on population, residence, and age. We then provide a detailed descriptive analysis of voting data from one particular entity: Te Rūnanga o Ngāti Awa, with whom we worked to understand how their elections inform their aspirations for continuing connectedness with tribal members. In the final section of the article, we present findings from an analysis of publicly available tribal voting data to see whether the trend of declining voter turnout is observable and whether online voting is shown to impact turnout.
Keywords: iwi elections; kaupapa māori research; māori voting; online voting; post-settlement (waitangi tribunal); self-determination

The Genesis of Maori Activism - Walker, Ranginui (Journal of the Polynesian Society, 1984)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: activism; iwi; land development; land tenure; parliament; rangatiratanga; rohe; self-determination; sovereignty; tiriti o waitangi/treaty of waitangi

Politics of Indigeneity: Challenging the State in Canada and Aotearoa New Zealand - Fleras, Augie; Maaka, Roger (Otago University Press, 2005)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: bicultural; government; government relations; kāwanatanga; native americans; self-determination; sovereignty; tino rangatiratanga; tāngata whenua

Mātauranga Māori, tino rangatiratanga and the future of New Zealand science - Broughton, D; McBreen, K (Journal of the Royal Society of New Zealand, 2015)
All peoples develop their own academic traditions: philosophies grounded in their experiences over successive generations, and theories for growing knowledge and wisdom. Mātauranga Māori (mātauranga) is the Indigenous knowledge system of these lands. It is dynamic, innovative and generative. The mātauranga continuum is the knowledge accumulated through this system. Government policies and systems have marginalised mātauranga and prioritised Western science, and the past 100 years have seen a slowing in the expansion of the mātauranga continuum. Unless the survival of mātauranga is prioritised, it will cease to flourish. Māori have discussed and written extensively about the ongoing impact of colonisation on mātauranga and tikanga Māori. This paper builds on those discussions, arguing for tino rangatiratanga, including Māori ownership of mātauranga, fulfilment of the government's obligations to Māori, and the reinstitution of mātauranga as a primary knowledge system in Aotearoa. It explains why mātauranga revitalisation is important and outlines some of the steps towards this goal. We are calling for Western academics to support mātauranga revitalisation, with the vision of two functional knowledge systems operating that are unique to New Zealand.
Keywords: mātauranga māori; self-determination; tino rangatiratanga

Self-Determination and Redistributive Justice: The New Zealand Māori - Sullivan, Ann (He Pukenga Korero: a journal of Māori studies, 1998)
Keywords: crown policy; mātauranga māori; rangatiratanga; self-determination; social life and customs; tiriti o waitangi/treaty of waitangi; tāngata whenua; welfare policies

Maori sustainable development in the 21st century: The importance of Maori values, strategic planning and information systems - Harmsworth, Garth; Barclay-Kerr, Kim; Reedy, Tamati (He Puna Korero: Journal of Maori & Pacific Development, 2002)
Keywords: autonomy; economic development; governance; rangatiratanga; self-determination

The changing images of nineteenth century Māori society: from tribes to nation - Henare, Manuka Arnold (2003)
Keywords: colonisation; he whakaputanga; history; self-determination; thesis; tino rangatiratanga; tiriti o waitangi/treaty of waitangi

The rights of indigenous peoples - Charters, Claire (New Zealand Law Journal, 2006)
Keywords: UNDRIP; māori rights; self-determination; tino rangatiratanga

Use It or Lose It: The Value of Using the Declaration on the Rights of Indigenous Peoples in Maori Political and Legal Claims - Charters, Claire (2017)
In this paper I argue that Maori should cite and rely on the Declaration on the Rights of Indigenous Peoples in their legal and political claims as this process can lead to the internalisation of these norms even when states reject them. The paper draws heavily on the case study of the use of the Declaration in a Waitangi Tribunal claim relating to Maori self-determination.
Keywords: UNDRIP; crown; indigenous rights; international law; mana motuhake; self-determination; waitangi tribunal

Legitimising the State: Constitutional Reform to Recognise Rangatiratanga and Tikanga Maori - Charters, Claire (2016)
Arguments for constitutional reform to recognise Rangatiratanga and Tikanga Maori.
Keywords: constitution; constitutional transformation; crown; crown policy; international law; law; self-determination; tikanga | indigenous law; tino rangatiratanga

A Self-Determination Approach to Justifying Indigenous Peoples' Participation in International Law and Policy Making - Charters, Claire (International journal on minority and group rights, 2010)
This paper defends the legitimacy-positive impact of a "contextual-participation approach" to indigenous peoples' participation in international law-making. It argues that indigenous peoples' participation should be substantial where the issue being negotiated at the international level is of considerable interest to indigenous peoples and indigenous peoples have not consented to state representation. The "contextual-participation approach" to indigenous peoples' participation realises the justice in indigenous peoples' claims to remedial efforts to recognise their, mostly lost and historical, sovereignty, and to contemporary and evolving legal, and largely democratic, understandings of self-determination, as expressed, for example, in the UN Declaration on the Rights of Indigenous Peoples. At the same time, it balances indigenous peoples' self-determination entitlements to full participation in international law making, as unjustifiably excluded sovereigns, with contemporary political realities.
Keywords: autonomy; crown law; human rights; indigenous rights; international law; international relations; justice; law; not sure if maori; participation; policy making; political activity; political participation; representation; right wing politics; rights; self-determination; sovereignty; united nations

Indigenous legal theory: some initial consideration - Benjamin J. Richardson; Charters, Claire (Indigenous peoples and the law: comparative and critical perspectives, 2009)
"Provides an historical, comparative and contextual analysis of various legal and policy issues affecting indigenous peoples. It focuses on the common law jurisdictions of Australia, Canada, New Zealand and the United States, as well as relevant international law developments"–Back cover.
Keywords: crown law; ethnic identity; international law; iwi taketake; law; print only; self-determination

Whānau, Tikanga and Tino Rangatiratanga: What is at stake in the debate over the Ministry for Children? - Fitzmaurice, Luke (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2020)
Keywords: crown policy; crown violence; discrimination; rangatiratanga; self-determination; tamariki; tikanga | indigenous law; waitangi tribunal

International indigenous rights in Aotearoa New Zealand - Erueti, Andrew (Victoria University Press, 2017)
Over the past four decades, international indigenous rights have become a prominent aspect of international law and are now enshrined in the UN Declaration on the Rights of Indigenous Peoples. Yet, while endorsed by Aotearoa New Zealand in 2010, little remains known about how these standards came about, how the international movement that created them was established, and the implications of these standards on national reforms already protecting Māori rights. International Indigenous Rights in Aotearoa New Zealand seeks to answer these questions. This collection of essays places the Declaration in the context of New Zealand rights around such issues as Treaty settlements, mining policy and the status of Māori children. Crucially, it also asks how Māori can hold New Zealand to account against international indigenous rights.
Keywords: UNDRIP; government relations; human rights; iwi taketake; law; self-determination; tikanga | indigenous law; tiriti o waitangi/treaty of waitangi; treaty claims

Indigenous Peoples’ Energy Projects - Bargh, Maria (2010)
There are increasing numbers of Māori in New Zealand and Aboriginal peoples in Canada involved in the energy sector. In this paper I explore a number of the factors which have been instrumental in Indigenous peoples becoming involved in energy projects. Utilising a ‘weak theory’ approach I provide narratives of three case studies from New Zealand and Canada (Tuaropaki Trust, Hupacasath First Nation, Peavine Métis Settlement). These cases involve renewable and non-renewable energy types – categories which are often used to judge the value of energy projects. I suggest that while these distinctions provide useful analyses, I ask what might happen if we extend the analysis further to consider how the apparent ‘negatives’ and ‘positives’ of each might be being balanced by other activities that the Indigenous companies are involved with.
Keywords: environment; land governance; land ownership; māori trusts; non-renewable energy; renewable energy; resource management; self-determination; tino rangatiratanga

Māori education and principles of self-determination in the twenty-first century. - O’Sullivan, Dominic (Waikato Journal of Education, 2001)
This paper argues that self-determination to the greatest extent possible is a legitimate aspiration for Maori people. It is argued that in education this requires a philosophical and policy response more focused on Maori autonomy than can be provided within the bicultural framework that has lately informed Maori relationships with other actors in the education arena. The paper considers the place of kohanga reo, kura kaupapa Maori and wananga in relation to broader Maori aspirations for self-determination and discusses proposals that these aspirations be furthered through the establishment of a Maori Education Authority. It is also argued that opportunities for self-determination in New Zealand are compromised by the government's unwillingness to alter a tightly controlled centralised education market to provide genuine Māori autonomy over what type of education might be available and to what end.
Keywords: crown policy; education; rangatiratanga; self-determination

Needs, rights, nationhood, and the politics of indigeneity - O’Sullivan, Dominic (MAI review, 2006)
In 2004 the appointment of a Coordinating Minister Race Relations, signalled a shift in elite Māori policy thinking from a long-standing cautious bipartisan acceptance of selfdetermination towards a re-emergent assimilationist ‘one law’ for all discourse. The question simplistically posed by the Leader of the Opposition was should welfare entitlements be granted on the basis of need or race (Brash 2004)? Beneath this question lies an ideological assumption which privileges assimilation over indigeneity as the basis of Māori participation in public affairs. This paper therefore asks: are Māori peoples with rights, or individuals with needs? Is there a deeper politics of indigeneity providing a legitimate foundation for rights which are not necessarily superior to the rights of citizenship, but are important and distinguishable adjuncts? These questions transcend the issue of welfare entitlements to wider questions about the nature and terms of Māori belonging to the liberal polity. The paper highlights the political tension between government attempts to remove indigeneity from the public agenda in response to populist pressure and a pragmatic acceptance that New Zealand ‘needs’ Māori to increase their contribution to the national economy and that the realisation of this goal may in fact depend on the fuller citizenship imagined by the politics of indigeneity.
Keywords: assimilation; indigenous rights; māori rights; rangatiratanga; self-determination

Maori self-determination and a liberal theory of indigeneity - O'Sullivan, Dominic (Restoring Indigenous Self-Determination: Theoretical and Practical Approaches, 2014)
Indigenous peoples find themselves locked in power struggles with states and transnational actors who resist their claims, raising important questions in theory and practice. Edited by Marc Woons.
Keywords: rangatiratanga; self-determination; sovereignty

Being Present: Embodying Political Relations in Indigenous Encounters with the Crown - Hoskins, Te Kawehau; Bell, Avril (Contemporary Political Theory, 2021)
Political encounters between settler governments and indigenous communities are freighted with the unresolved issues of indigenous independence asserted under ongoing conditions of colonial domination. Within political science, these encounters have been primarily theorised and analysed as struggles of indigenous communities for political recognition from settler states. Further, the politics of recognition is widely understood as colonising by indigenous scholars, with some arguing for an alternative politics of (indigenous) resurgence and refusal, a ‘turning away’ from the state. In this article, we argue that in the case of Ma¯ori in Aotearoa ‘turning up’ is the ethical and correct practice of politics, a practice stemming from the relational ontology of the Ma¯ori world. Thus ‘turning up’ rather than ‘turning away’ can, for Ma¯ori, itself be a practice of refusal. We outline the centrality of the embodied, face-to-face encounter within Ma¯ori politics, and identify the ongoing presence of the sovereign’s body and embodiment more broadly within the Westminster tradition, as symbolised in the concept of the Crown. Building on these compatibilities within distinct political ontologies, we argue for the potential and productivity of face-to-face political encounters, and call on the New Zealand Crown to also prioritise ‘turning up’ in its engagement with indigenous communities.
Keywords: kāwanatanga; rangatiratanga; self-determination

Decolonisation starts in a name: Moving on from the colonial pretence that 'Maori' or 'indigenous peoples' are explanatory frames - MacDonald, Lindsey Te Ata o Tu (Political Science, 2016)
This article examines why and how scholars should acknowledge and name each of the diverse political actors and institutions that typically are objectified as ‘indigenous peoples’ on the global stage, or ‘Māori’ in New Zealand. For instance, rather than suggesting a political relationship or conflict exists between ‘Māori and the Crown’, political scientists and theorists should name the political actors and political institutions for which Māori is a shorthand, for example, ‘Te Runanga o Ngai Tahu (the corporate entity of the Ngai Tahu whanui) and the Committee of Tuahiwi Marae disagreed with the Crown’. A variety of reasons are discussed as to why this objectification of Māori (and any other indigenous population) as a single political actor has occurred, the problems are pointed out, and a range of examples are given. Not every use of the terms ‘Māori’, ‘indigenous peoples’ or similar descriptors in political science stands in for a specific political actor (e.g. sometimes, it is suggesting a cleavage or a group at whom a policy is directed), but where scholars are describing or suggesting political action, they should be careful in their use of ethnic labels. I suggest that it would be more productive to study the specific contexts, intentions and actions of individuals and institutions that might consider indigeneity as being part of their identity.
Keywords: decolonisation; mana wāhine; self-determination

The diverse stories of Māori political agency: a Q method study - Sheed, Toni; MacDonald, Lindsey Te Ata o Tu (Political Science, 2017)
While there is much research and writing on Māori self-determination, little of it focuses on how Māori individuals and organisations conceive the necessary antecedent to self-determination; Māori political agency. To remedy this research gap, we explored the political aspirations of Māori individuals with a research method built to study such subjective topics: Q method. Combining Q method with some practical innovations from Kaupapa Māori Research method, we developed a unique way of researching the stories our participants tell themselves about politics. Our results suggest some Māori individuals do think of politics as a collective endeavour as the self-determination literature suggests, but just as often Māori collective forums and other non-Māori political institutions are seen as barriers to Māori individual and collective political agency and thus to Māori self-determination. We also found that Māori view the political autonomy and participation necessary for self-determination as possible in numerous diverse spaces, suggesting the focus on low voter turnout amongst Māori in the literature is missing the point: the stories told by this research suggest Māori individuals perceive their political agency to be hindered, not by majoritarian politics of non-Māori, but by Māori and non-Māori elites.
Keywords: mana motuhake; political agency; self-determination; tino rangatiratanga

Rangatiratanga: Narratives of Racism, Resistance, and Well-being - Smith, Dr Cherryl; Tinirau, Rāwiri; Rattray-Te Mana, Helena; Moewaka Barnes, Helen; Cormack, Donna; Fitzgerald, Eljon (Whanganui: Te Atawhai o Te Ao., 2021)
Keywords: colonisation; racism; rangatiratanga; self-determination; wellbeing

Tino Rangatiratanga and Well-being: Māori Self Determination in the Face of Covid-19 - Te One, Annie; Clifford, Carrie (Frontiers in sociology, 2021)
The New Zealand government has been globally praised for its response to Covid-19. Despite the global accolades, little attention has been given to the swift and innovative Māori response to Covid-19. This paper will detail some of this rapid Māori response to Covid-19 in Aotearoa New Zealand and argue the response can be understood as key examples of Māori exercising tino rangatiratanga (self-determination), independent of the government's measures and policies. We suggest that this exploration of tino rangatiratanga during Covid-19 demonstrates central aspects of Māori well-being that move beyond a government focus on statistics as the key measure of well-being and how tikanga Māori (Māori values) are being used to develop successful responses to the global pandemic.
Keywords: covid-19; hauora; health; māori health; self-determination; sociology; tikanga | indigenous law; tino rangatiratanga

Indigenous Peoples' Data During COVID-19: From External to Internal - Carroll, Stephanie Russo; Akee, Randall; Chung, Pyrou; Cormack, Donna; Kukutai, Tahu; Lovett, Raymond; Suina, Michele; Rowe, Robyn K. (Frontiers in Sociology, 2021)
Global disease trackers quantifying the size, spread, and distribution of COVID-19 illustrate the power of data during the pandemic. Data are required for decision-making, planning, mitigation, surveillance, and monitoring the equity of responses. There are dual concerns about the availability and suppression of COVID-19 data; due to historic and ongoing racism and exclusion, publicly available data can be both beneficial and harmful. Systemic policies related to genocide and racism, and historic and ongoing marginalization, have led to limitations in quality, quantity, access, and use of Indigenous Peoples' COVID-19 data. Governments, non-profits, researchers, and other institutions must collaborate with Indigenous Peoples on their own terms to improve access to and use of data for effective public health responses to COVID-19.
Keywords: colonisation; covid-19; data; data sovereignty; inequity; racism; self-determination

Recognition and indigenizing official statistics: Reflections from Aotearoa New Zealand and Australia - Kukutai, Tahu; Walter, Maggie (Statistical Journal of the IAOS, 2015)
In First World colonised nations such as Aotearoa New Zealand and Australia, population statistics form the evidentiary base for how Indigenous peoples are known and `managed' through state policy approaches. Yet, population statistics are not a neut
Keywords: colonisation; crown policy; data sovereignty; identity; policy; self-determination; statistics

Chapter 2: "Publishing the Space": Data sovereignty and self-determination in Aotearoa New Zealand - Kukutai, Tahu; Cormack, Donna (Indigenous Data Sovereignty and Policy, 2020)
This book examines how Indigenous Peoples around the world are demanding greater data sovereignty, and challenging the ways in which governments have historically used Indigenous data to develop policies and programs. In the digital age, governments are increasingly dependent on data and data analytics to inform their policies and decision-making. However, Indigenous Peoples have often been the unwilling targets of policy interventions and have had little say over the collection, use and application of data about them, their lands and cultures. At the heart of Indigenous Peoples’ demands for change are the enduring aspirations of self-determination over their institutions, resources, knowledge and information systems. With contributors from Australia, Aotearoa New Zealand, North and South America and Europe, this book offers a rich account of the potential for Indigenous data sovereignty to support human flourishing and to protect against the ever-growing threats of data-related risks and harms.
Keywords: colonisation; data sovereignty; policy; self-determination